Estimating prevalence and identifying predictors of zero-dose pentavalent and never-immunized children under two years of age in Kashmore and Sujawal Districts of Sindh, Pakistan: An analysis of household survey data - Danya Arif Siddiqi; Manaksha Memon; Sundus Iftikhar; Muhammad Siddique; Vijay Kumar Dharma; Ahsan Ahmad; Nauman Safdar; Mubarak Taighoon Shah; Hamidreza Setayesh; Irshad Ali Sodhar; Farrukh Raza Malik; Subhash Chandir (PLoS ONE, 2025)
Introduction Despite intensified global efforts to enhance immunization coverage, one in five children continue to miss out on life-saving vaccines, leaving them vulnerable to a range of vaccine-preventable diseases. In 2022, 14.3 million children failed to receive even a single dose of the pentavalent vaccine (Penta-1) by their first birthday, classified as “zero-dose penta”. Additionally, some children have not received any vaccinations at all and have had no contact with healthcare services—these are referred to as “never-immunized” children. Collectively, both groups—zero-dose penta and never-immunized children—are termed “true zero-dose” to emphasize the critical need for targeted interventions that ensure no child is left behind in immunization efforts. Methods We conducted a household (HH) survey from August 10 to December 19, 2022, in Kashmore and Sujawal, two districts in Sindh, Pakistan, with low immunization coverage. The survey targeted children aged 12−23 months who had not received the Penta-1 vaccine by their first birthday. Our study aimed to determine the community-based prevalence of zero-dose penta and never-immunized children, compare their sociodemographic characteristics and immunization histories, and identify predictors of these outcomes. Results Of the 2,091 children surveyed, 497 (23.8%) were zero-dose penta, and 587 (28.1%) were never-immunized. Together, these groups constitute 51.9% of the survey population, referred to as ‘true zero-dose’. The remaining 1,007 (48.1%) were either fully or partially immunized. Multivariate analysis indicated that absence of antenatal care (ANC) significantly increased the risk of children being classified as zero-dose penta (RRR = 1.68; 95% CI: 1.04–2.72; p < 0.035) and never-immunized (RRR = 2.07; 95% CI: 1.25–3.45; p < 0.005). Furthermore, the absence of Lady Health Worker (LHW) visits significantly increased the risk of children being classified as zero-dose penta (RRR = 2.55; 95% CI: 1.26–5.16; p < 0.009), and the absence of vaccinator visits significantly increased the risk of being never-immunized (RRR = 4.44; 95% CI: 2.68–7.36; p < 0.001). Conclusion Despite global efforts for achieving universal immunization, half of the surveyed children remained true zero-dose, highlighting significant gaps in the ability of immunization programs to reach underserved communities. To address this issue, it is essential to enhance ANC coverage and leverage frontline health workers (FHWs) to identify and engage with clusters of zero-dose children effectively. These measures will ensure that no child is left behind, advancing health equity and safeguarding future generations.